Highly selective claisen-schmidt condensation catalyzed by silica chloride under solvent-free reaction conditions - Hazarkhani, Hassan; Kumar, Pradeep; Kondiram, Kadam Sachin; Gadwal, Ikhlas M. Shafi (Synthetic Communications, 2010)
Silica chloride serves as a useful catalyst in the cross-aldol condensation, leading to the synthesis of a wide variety of bisarylidene cycloalkanones and chalcones. The catalyst showed high selectivity; self-condensation of ketones was not observed.
Keywords: Aldol reaction; arylidene cycloalkanone; Claisen-Schmidt; condensation; silica chloride

Simple and efficient synthesis of 2-Aryl-2,3-dihydroquinolin-4(1H)-ones using silica chloride as a new catalyst under solvent-free conditions - Muthukrishnan, Murugan; Mujahid, Mohammad; Punitharasu, V.; Dnyaneshwar, D. A. (Synthetic Communications, 2010)
A mild, efficient, and high-yielding method for the synthesis of 2-aryl-2,3-dihydroquinolin-4(1H)-ones from their corresponding 2-amino chalcones using silica chloride (SiO2Cl) under solvent-free conditions is described. A series of 2-aryl-2,3-dihydroquinolin-4(1H)-ones containing both electron-donating and electron-withdrawing substituents were synthesized.
Keywords: 2-Amino chalcones; 2-aryl-2; 3-dihydroquinolin-4(1H)-ones; Microwave; silica chloride